2023
DOI: 10.1002/ps.7675
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antibacterial and antifungal activity of myricetin derivatives containing piperidine and amide fragments

Abstract: BACKGROUNDContinuous use of synthetic bactericides and fungicides is causing pathogens to develop resistance, resulting in increased use of pesticides and affecting food security. The green pesticides derived from natural products could reduce or avoid ‘pesticide hazards’ caused by synthetic pesticides as a result of their unique mechanism of action. Therefore, it is of great significance to create green pesticides with novel structures.RESULTSHerein, 30 novel myricetin derivatives containing piperidine and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The inhibitory activity of Y1–Y22 against ten phytopathogenic fungi was tested according to refs . Refer to the Supporting Information for detailed steps.…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory activity of Y1–Y22 against ten phytopathogenic fungi was tested according to refs . Refer to the Supporting Information for detailed steps.…”
Section: Methodsmentioning
confidence: 99%
“…Defense Enzyme Activity Evaluation. 35,36 Catalase (CAT), superoxide dismutase (SOD), and peroxidase (POD) activities were assessed using the defense enzyme assay kit from Suzhou Keming Bioengineering Institute, China, following the instructions of the manufacturer. Initially, two Ps cakes, each with a diameter of 5 mm, were placed in a conical flask containing 50 mL of the PDB medium.…”
Section: Morphological Observation By Fluorescence Microscopy (Fm)mentioning
confidence: 99%
“…[23][24] Flavonols and quinazolinones have a wide range of biological activities, the active splicing method has been widely used in the development of new pesticides. [25][26][27] Therefore, 20 flavonol derivatives containing quinazolinone were designed, synthesized and evaluated for their antiviral activity by using the natural product flavonol as a lead compound and introducing quinazolinone moiety (Figure 1). Bioassays demonstrated that K5 exhibited the better antiviral activity compared with that of NNM.…”
Section: Introductionmentioning
confidence: 99%